Postcolonial Trauma in Vietnamese American Fiction - Vokálová, Lucie (Univerzita Pardubice, 2025)
This diploma thesis explores the theme of postcolonial trauma in Vietnamese American fiction, focusing on the novels On Earth We're Briefly Gorgeous by Ocean Vuong and The Gangster We Are All Looking For by L? Thi Diem Thúy. The thesis provides a brief overview of Vietnamese literature and immigration and places both authors within a relevant cultural and historical context. It also outlines key concepts of postcolonial criticism, with particular attention to postcolonial trauma. The two novels are analyzed mainly in terms of war-related trauma (including PTSD and its intergenerational effects), hybridity, subalternity, and otherness. Furthermore, the thesis examines the use of figurative language and non-linear narrative structures as tools for expressing trauma. The aim of this thesis is to show how postcolonial trauma is articulated in different ways within Vietnamese American fiction.
Postkoloniální trauma ve vietnamsko-americké beletrii
Keywords: Američané vietnamského původu; OEWBG; The Gangster; trauma; Vietnamese Americans; OEWBG; The Gangster; trauma